HISTORICAL AND ARCHAEOLOGICAL TOURISM IN NAMANGAN REGION - Zafarjon Nazarov (Journals Park Publishing, 2022)
This article discusses historical and archaeological tourism in Namangan region. Also, an opinion was expressed about the study of Ahsikent, Munchoktepa, Mugtepa, Uchtepa as an important object of architectural monuments, and the tourism areas that can be developed in these areas and their surroundings today.
Keywords: tourism, archeology, Akhsikent, Munchogtepa, Mugtepa, Uchtepa, cultural heritage, economy